Breast tumors: computer-assisted quantitative assessment with color Doppler US - Huber, Sabine; Delorme, Stefan; Knopp, Michael V.; Junkermann, Hans; Zuna, Ivan; Fournier, Dietrich von; Kaick, Gerhard van (Radiology, 1994)
PURPOSE: To compare quantified measurements with color Doppler ultrasonography (US) with those obtained with conventional duplex US in the differential diagnosis of suspect lesions in the breast. MATERIALS AND METHODS: A computer-assisted protocol was used to calculate the color pixel density (CPD) and the mean color value (MCV) in US images of breast lesions. These results were compared with conventional results in the examination of 25 patients (aged 29-78 years) with carcinomas and 32 patients (aged 23-73 years) with benign lesions of the breast. RESULTS: The sensitivity of maximum flow velocity in helping identify carcinomas was 60% and the specificity was 70%. In color Doppler US, the sensitivity for MCV in helping identify carcinomas was 92% and the specificity was 78%; for CPD the sensitivity was 64% and the specificity was 91%. Combining MCV and CPD did not improve differentiation. CONCLUSION: Computer-assisted image analysis may be superior to conventional duplex US in helping differentiate between carcinomas and benign lesions.
Gesehen am 19.02.2025